(untitled) (Journal of International Crisis and Risk Communication Research, 2022)
After-action reports are important texts that make sense of moments of crisis and restore organizational order. We add to existing research on these reports by incorporating the rhetorical concepts of terministic screens and the pentad to understand how reports commemorate disorder and organizational trauma. Analyzing the multiple reports created after the 2017 Las Vegas Shooting, we find that reports from different professional fields commemorate crises in disparate ways that select and deflect memories of trauma. This study extends risk and crisis studies of crisis documentation by highlighting the emotional role reports play in making sense of organizational trauma and considering how professional fields influence post-crisis rhetoric of renewal.